If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9y + 42 = 2(y + 7) Reorder the terms: 42 + 9y = 2(y + 7) Reorder the terms: 42 + 9y = 2(7 + y) 42 + 9y = (7 * 2 + y * 2) 42 + 9y = (14 + 2y) Solving 42 + 9y = 14 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 42 + 9y + -2y = 14 + 2y + -2y Combine like terms: 9y + -2y = 7y 42 + 7y = 14 + 2y + -2y Combine like terms: 2y + -2y = 0 42 + 7y = 14 + 0 42 + 7y = 14 Add '-42' to each side of the equation. 42 + -42 + 7y = 14 + -42 Combine like terms: 42 + -42 = 0 0 + 7y = 14 + -42 7y = 14 + -42 Combine like terms: 14 + -42 = -28 7y = -28 Divide each side by '7'. y = -4 Simplifying y = -4
| 2.1a+1.25=-9.04 | | 5.9x=-57.23 | | 9=2(y-8)-7y | | -3v+5(v+2)=14 | | 5.9x=57.23 | | 9+3x=6-2x | | x-6=3.53 | | 8x+4x-17=-53 | | 480x=120x^2 | | 26=-12v-9+7v | | 5(k-3)-6=4k-(3k-2) | | 6w-13w-18=-81 | | 10-3(m-2)=7 | | 4x-13=2(3-x) | | 5w+27+4w=9 | | 8-2t=14+t | | 2(2y-1)+y=5(y+3) | | -9x+5(-3x-4)=-42-2x | | 40+40*0+1= | | 2x+7(3x-4)=-2-3x | | -8x^2+24x-18= | | -16+x=450 | | 5x^2+50x=0 | | -5x+x=-16 | | 120x^2-272x+120=0 | | 5*5*5*5= | | 2t^2+2t=3 | | 10-3(-8-2)= | | 120x^2-272x+102=0 | | 10x-0.375-4x=6x | | 2+x=16-6x | | 30a=2a-8 |